Economics of our free enterprise system - Brown, Kenneth W; Warner, Allen R; Darby, Dorothy J. (New York : Gregg Division, McGraw-Hill, 1982)
Discusses the elements of our free enterprise system and how it works in the world economy.
Keywords: Economics; United States -- Economic conditions